“Where Shall I Take my Grief?” National Space in Yaakov Steinberg՚s Poetry Steinberg՚s Poetry - Elhanan, Elazar (MiKAN, 2022)
The article historicizes and contextualizes the “marginality” of the poet Yaakov Steinberg, in relation to his rejection of the basic poetic assumptions associated with Hebrew national culture. It describes how authors of the Hebrew renaissance appropriated practices from Russian symbolist poets to craft a poetic system adequate to the representation of a desired national existence: the consolidation of the fragmented Jewish national body. This poetic system also defined any divergence from it as artistically inferior and mentally unsound. Yaakov Steinberg (1886-1947), a prominent Hebrew and Yiddish poet, rejected this national poetics and his work offers a complex parody of it. Using a decadent aesthetics of decline and fragmentation to reflect his affiliation to a pan-European, internationalist experience, he was reviled and marginalized. Steinberg’s subversion of national poetics, the article claims, aimed to debate the theory underlying the concept of a national culture, while suggesting an alternative formulation of modernity, grounded in decadent aesthetics and rejecting the rendering of the Jewish literary space as monolingual. This alternative is strongly connected to the history of Yiddishism and the heated debate in the Zionist movement over the value of “the work of the present”.